Pembuatan Alat Pendeteksi Dini Wereng Batang Coklat Secara Sederhana di Desa Tanggalrejo - Nasirudin, Mohamad; Suhadi, Agus; Indah Yuliana, Anggi; Ario Wibowo, Rendy; Nur Cahaya , Fitria; Hari Winarno, Dwi; Maf'ulah, Siti (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
The rice crop yields in Daterejo Village are erratic from year to year, and farmers often suffer losses. The outbreak of brown planthoppers is one of the threats feared by rice farmers in Daterejo Village. The community service carried out aims to provide knowledge on how to detect early and control brown planthoppers in rice cultivation areas. Service activities were carried out in Daterejo Village, Mojoagung District, Jombang Regency, East Java Province. Implementation of community service activities will be carried out in September 2023. The implementation method for this community service activity uses the Participatory Action Research method. Action and participatory methods are implemented in socialization activities among farmer groups and also training in operationalizing the brown planthopper early detection tool. The community service carried out is by implementing appropriate technology for early detection of brown planthopper insect pests. This early detection tool for insect pests actually has several benefits, including knowing the population of brown planthopper pests in rice clumps. In the socialization, tools for detecting insect pests in rice clumps were explained, and the life cycle of brown planthopper pest insects on rice plants. The hope is that farmers will be able to detect it early when rice planting is taking place, so that there will be no crop failure caused by attacks by brown planthopper pests.